2021
DOI: 10.24200/sci.2021.55579.4291
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study on Couple Stress Fluid in an inclined Channel

Abstract: Numerical and analytical solutions of Stokes theory of couple stress fluid under the effects of constant, space, and variable viscosity in the inclined channel are discussed here. The considered couple stress fluid is described mathematically with the definition of the stress tensor. The dimensional form of the boundary value problem is transformed into dimensionless form by defining dimensionless quantities and then solved with help of the perturbation technique. The analytical expressions of velocity and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A review of couple stress fluid dynamics was reported by Stokes [4] in 1984. The presence of couple stress parameter decreases the velocity of the fluid and other parameters effect on the velocity of a single couple stress fluid studied by Devakar et al [5], Ahmad [6], and Jangili et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…A review of couple stress fluid dynamics was reported by Stokes [4] in 1984. The presence of couple stress parameter decreases the velocity of the fluid and other parameters effect on the velocity of a single couple stress fluid studied by Devakar et al [5], Ahmad [6], and Jangili et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Chebyshev trial function provides a very good approximation for the uncoupled problem. Moreover, for the Coupled system when α = 0, tables for the comparison of the numerical solutions by spectral collocation and the Runge-Kutta-Fehlberg (RKF) integration technique are presented for Equations (12) and (13). In Tables 2 and 3, the error ranges from 10 −17 and 10 −8 for Equation (12) which means that the two results converge to one.…”
Section: Resultsmentioning
confidence: 99%
“…Yusuf et al [12] also presented a semi-analytical solution on a micropolar fluid flow over an inclined geometry with velocity slip. Very recently, Ahmad et al [13] analytically examined Stoke's theory of couple stress fluid over an inclined channel under variable viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiphase flow suspended with Hafnium particles is better than the one with crystal particles. Ahmad et al 28 examined the analytical study on a couple stress fluid in an inclined channel. Finite element simulations of free convection flow inside a porous inclined cavity filled with micropolar fluid reported by Ali et al 29 The entropy analysis in the Rabinowitsch fluid model through the inclined wavy channel was explained by Nazeer et al 30 Numerical simulations of MHD flow of micropolar fluid inside a porous inclined cavity with uniform and nonuniform heated bottom studied by Nazeer et al 31 The impact of slip boundary conditions, magnetic force, and porous medium on blood flow of Jeffrey fluid discussed by Nazeer et al 32 Mathematical modelings and simulation of MHD electro‐osmotic flow of Jeffrey fluid in convergent geometry reported by Nazeer et al 33 Saleem et al 34 depicts the theoretical study of electro‐osmotic multiphase flow of Jeffrey fluid in a divergent channel with lubricated walls.…”
Section: Introductionmentioning
confidence: 99%